Espaço, tempo e infância: problematizações acerca do artefato midiático Barbie - Diniz, Kênia Mendonça (2014)
This study investigated how and what Barbie wants to teach children about the contemporary post-modern capitalism world through analysis of two films, Barbie: A Estrela do Rock (1987) and Barbie: A Princesa & A Pop Star (2012). We aim to understand the relationship established between the Barbie and the binomial time and space within the post - modern. We understand that Barbie, despite sharing the characteristics and physical features of an adult, is clearly commercially directed at a child target audience. Therefore we turned our attention to establishing a link between the contemporary, consumer society, childhood, space and time and we related these elements to the visual language and to the cinematic aesthetics. Children are meant to see Barbie as an archetype of the woman they aspire to be in the future. It is a character who not only teaches them rules of fashion, but an entire lifestyle and behavior, and also teaches them a way of seeing and being in the world. Barbie supposedly always seeks to teach good ethics to its target audience. Thus, our intention with this work was to analyze the filmic artefacts in order to understand the subtleties presented through them and to provide elements of reflection in education that are especially trying to understand the extent of the teachings given by Barbie. These artefacts need to be considered as more than just superficial beauty, kindness and generosity. Our research identified that Barbie is a character that teaches children about the contemporary world. And this, thanks to the invention and reinvention of the capitalism system, still seems important to teach girls to feed the dream of being a princess and dressing themselves in pink dresses. So, we can see how Barbie became a globalised protagonist as a consequence of this capitalism that wants to be constantly established and reinstated. And Barbie has been performing its function masterfully, stimulating increasingly its audience, especially the children to strengthen their capitalist interests; generating consumption in accordance to the characteristics that underlie the post-modern society.